The History and Applications of the Veterans RAND 12-Item Health Survey (VR-12). Issue 3 (July 2022) - Selim, Alfredo J.; Rothendler, James A.; Qian, Shirley X.; Bailey, Hannah M.; Kazis, Lewis E.
Abstract : There has been an increasing emphasis on placing patients at the center of clinical care and health care research and, in particular, assessing outcomes and experiences from the patient's perspective. One of the most widely used patient-reported outcome instruments is the Veterans RAND 12-item Health Survey (VR-12). This article reviews the VR-12 development and its applications over the last 2 decades, including research and potential uses in clinical care.